Highest Common Factor of Polynomials by Factorization

How to find the highest common factor of polynomials by factorization?

Let us follow the following examples to know how to find the highest common factor (H.C.F.) or greatest common factor (G.C.F.) of polynomials by factorization.

Solved examples of highest common factor of polynomials by factorization:

1. Find out the H.C.F. of a2b + ab2 and a2c + abc by factorization.

Solution:

First expression = a2b + ab2

                      = ab(a + b)

                      = a × b × (a + b)

Second expression = a2c + abc

                          = ac(a + b)

                          = a × c × (a + b)

It can be seen, in both the expressions ‘a’ and ‘(a + b)’ are the common factors and there is no other common factor.

Therefore, the required H.C.F. a2b + ab2 and a2c + abc is a(a + b)



2. Find the out the H.C.F. of (a2b + a2c) and (ab + ac)2 by factorization.

Solution:

First expression = a2b + a2c

                      = a2(b + c)

                      = a × a × (b + c)

Second expression = (ab + ac)2

                          = (ab + ac) (ab + ac)

                          = a(b + c) a(b + c)

                          = a × a × (b + c) × (b + c)    

It can be seen that, in both the expressions ‘a’, ‘a’ and ‘(b + c)’ are the common factors and there is no other common factor.

Therefore, the required H.C.F. is a × a × (b + c) = a2(b + c).



3. Find the out the H.C.F. of c(a + b)2, (a2c2 – b2c2) and a(ac2 + bc2) by factorization.

Solution:

First expression = c(a + b)2

                      = c × (a + b) × (a + b)

Second expression = (a2c2 - b2c2)

                          = c2(a2 - b2)

                          = c2(a + b) (a - b)

                          = c × c × (a + b) × (a - b)

Third expression = a(ac2 + bc2)

                       = ac2(a + b)

                       = a × c × c × (a + b)

It can be seen that, c and (a + b) are the common factors of the expressions.

Therefore, the required H.C.F. of c(a + b)2, (a2c2 – b2c2) and a(ac2 + bc2) is c(a + b)



4. Find out the H.C.F. of 3x2(y + z)2 and 6x(y2 - z2) by factorization.

Solution:

First expression = 3x2(y + z)2

                      = 3x2 (y + z)(y + z)

                      = 3 × x × x × (y + z) × (y + z)

Second expression = 6x(y2 - z2)

                          = 6x(y2 - z2)

                          = 6x(y + z) (y - z)

                          = 2 × 3 × x × (y + z) × (y - z)

Therefore, the required H.C.F. is 3 × x × (y + z) = 3x(y + z)






8th Grade Math Practice

From Highest Common Factor of Polynomials by Factorization to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.